University Qualitative Education: An Instrument of National Integration and Sustainable Development in Nigeria - OLOFINNIYI, Olaiya Emmanuel; ADEKUNLE, Samuel Adekunle; ADEWARA , Oluwasegun Seun (International Journal of Educational Management, 2025)
Education serves as an instrument for promoting socio-economic, political, integration and cultural development of any nation. Hence, this paper examined the role of university qualitative education as an agent of integration and development. The paper posited that one of the major factors that deter national integration and unity in Nigeria is the inability of many Nigeria citizens to demonstrate core national values of patriotism, tolerance in terms of (politics, social, ethnic and religion); cooperation, honesty and obedience. It was discussed in the paper that presently, value for wealth, materialism, religion and ethnic loyalty are prominent among a number of Nigerians while civic values that can promote unity are relegated to the background. However, Nigeria cannot attain national integration that could foster expected development and national transformation without acquiring quality education and demonstrate required values and traits most especially in the University system. It was noted that appropriateness of educational qualities in the university system will enhance unity in culture, religion, politics, social and economic transformation since no nation can develop beyond the quality of its education. Therefore, tolerance, co-operation and f eeling of brotherhood should guide one in maintaining the national unity of our country through quality training in the university's education. This is expected to foster the desired sustainable development in Nigeria.